Notes on non-voting shares rights - Hernández Gazzo, Juan Luis (2022)
Although the regulation of non-voting shares in the General Corporations Law is generally adequate, there are some aspects related to the rights conferred to their holders that have generated discussion in recent years. We refer to the content of the preferential dividend that corresponds to non-voting shares, as well as the residual voting right in special meetings and the scope of the preferential subscription right that corresponds to them. This article provides an opinion on the treatment that these rights should have, so as to contribute to a greater use of the figure of non-voting shares as a mechanism of capitalization and financing in corporations.